2000
DOI: 10.1007/s004680000058
|View full text |Cite
|
Sign up to set email alerts
|

Controlled inoculation of Norway spruce (Picea abies) with Sirococcus conigenus: PCR-based quantification of the pathogen in host tissue and infection-related increase of phenolic metabolites

Abstract: Controlled inoculation of spruce seedling needle crowns and of shoots of 4-year-old spruce trees by Sirococcus conigenus led to disease symptoms (discoloration and necrosis) and to the induction of phenolic metabolites. Even upon complete infection, as proved by reisolation of the pathogen from inoculated seedlings, only 40% of the plants developed visible disease symptoms after 38 days. A Sirococcus-specific polymerase chain reaction (PCR) primer pair, SIRO1 and SIRO6, was designed based on sequences of a RAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 16 publications
(18 reference statements)
1
33
0
Order By: Relevance
“…)catechin and different flavonoids (astragalin, quercitrin, hyperin), and in P. abies (taxifolin monoglycoside, (? )catechin, picein) have also been reported from other studies (Bahnweg et al 2000;Oleszek et al 2002;Lieutier et al 2003;Roitto et al 2003;Turtola et al 2006;Zeneli et al 2006;Räisänen et al 2008). However, our analysis revealed that some glycosides were simply new or differed from previous studies.…”
Section: Discussionsupporting
confidence: 59%
“…)catechin and different flavonoids (astragalin, quercitrin, hyperin), and in P. abies (taxifolin monoglycoside, (? )catechin, picein) have also been reported from other studies (Bahnweg et al 2000;Oleszek et al 2002;Lieutier et al 2003;Roitto et al 2003;Turtola et al 2006;Zeneli et al 2006;Räisänen et al 2008). However, our analysis revealed that some glycosides were simply new or differed from previous studies.…”
Section: Discussionsupporting
confidence: 59%
“…contained higher concentrations of constitutive phenolics than those from low altitudes (below 500 m a.s.l. ), while the low altitude provenances showed a strong induction of phenolics in response to infection (Bahnweg et al 2000). This suggests that some forest trees may show genetic trade-offs between allocation to constitutive and induced phenolic responses to pathogens.…”
Section: Variation In Phenolics and Resistance Due To Plantinherent Fmentioning
confidence: 91%
“…Moreover, constitutive and inducible phenolics, such as (+)-catechin or taxifolin, were found to vary among spruce clones of different susceptibility to Ceratocystis polonica (Evensen et al 2000). In Norway spruce needles, accumulation of the glucoside picein in response to inoculation with Sirococcus conigenus, which causes shoot blight and cankers of various conifers, was reported to depend on provenance (Bahnweg et al 2000). The phenolic content seemed to be provenance and altitude dependent.…”
Section: Variation In Phenolics and Resistance Due To Plantinherent Fmentioning
confidence: 99%
“…Sm. (Filion et al 2003), as well as for a spruce pathogen in the presence of other pathogens (Bahnweg et al 2000).…”
Section: Monitoring and Quantification Of Pathogensmentioning
confidence: 99%